MENGENAL SEJARAH OTONOMI DAERAH DALAM SISTEM PEMERINTAHAN DAERAH - Eviandi Ibrahim (Ensiklopedia of Journal, 2021)
This national policy regarding regional autonomy and regional government has been stated in the form of Law Number 23 of 2014 concerning Regional Government. In principle, the regional autonomy policy is carried out by decentralizing the powers that have been centralized in the hands of the central government. In the decentralization process, the power of the central government was transferred from the central level to the local government as appropriate, resulting in a shift of power from the center to districts and cities throughout Indonesia. If in the original condition the flow of government power moved from the regions to the central level, it would be idealized that since the implementation of the regional autonomy policy, the flow of power dynamics would move the other way around, namely from the center to the regions.Keywords: Relations, Central Government, Local Government.